2010
DOI: 10.1039/c0nj00085j
|View full text |Cite
|
Sign up to set email alerts
|

Resolution of a configurationally stable [5]helquat: enantiocomposition analysis of a helicene congener by capillary electrophoresis

Abstract: Racemic [5]helquat as a triflate salt has been synthesized using a robust, three-step procedure. Subsequent exchange of triflate anions for inexpensive (R,R)-dibenzoyltartrate anions via an ion exchange resin afforded two diastereoisomeric salts. Crystallization led to the resolution of the helquat (ee 4 98%). This is the first time that a non-racemic helquat has been obtained; its helicity having been assigned and its racemization barrier determined. Capillary electrophoresis with a sulfated b-cyclodextrin ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 105 publications
(10 reference statements)
0
40
0
Order By: Relevance
“…[18] This resolution gave enantiopure [P-1][TfO] 2 in milligram quantities. During our studies on helquats, [12,18] we realized that the preparative power of PC to separate enantiomers of helical aromatics in multigram quantities is attractive and remains unexplored. Because of this, we became interested in the demonstration of the mass throughput advantage of this method with our helicene-viologen hybrids such as [1][TfO] 2 .…”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…[18] This resolution gave enantiopure [P-1][TfO] 2 in milligram quantities. During our studies on helquats, [12,18] we realized that the preparative power of PC to separate enantiomers of helical aromatics in multigram quantities is attractive and remains unexplored. Because of this, we became interested in the demonstration of the mass throughput advantage of this method with our helicene-viologen hybrids such as [1][TfO] 2 .…”
Section: Resultsmentioning
confidence: 98%
“…To this end, we started with slightly enantiomerically enriched [1][TfO] 2 (100 mg, 7.6 % ee in favor of the P enantiomer) and attempted PC with seeds of enantiopure (+)-[P-1]-[TfO] 2 (0.7 mg), which was obtained by our dibenzoyltartrate resolution route. [18] Solids collected from this crystallization experiment (15 mg) had an ee value of over 85 %, which showed that [1][TfO] 2 indeed forms a conglomerate. With this information in hand, we went on to develop a PC protocol for 1 on a 10 g scale.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations